Simulating the Macroeconomic Impact of Future Water Scarcity - Roson, Roberto (World Bank, Washington, DC, 2017)
In this paper we consider some of the economic implications of climate change scenarios as described in the Shared Socioeconomic Pathways (SSPs). By comparing potential water demand with estimates of (sustainable) water availability in different regions, we identify regions that are likely to be constrained in their future economic growth potential by the scarcity of water resources. We assess the macroeconomic impact of water scarcity under alternative allocation rules finding that, by assigning more water to sectors in which it has a higher value, shifting production to less water intensive sectors, and importing more water intensive goods, constrained regions can effectively neutralize these water related climate risks and adapt to a changing water environment. However, this adaptation effort is likely to imply some radical changes in water management policies.